2009
DOI: 10.1074/jbc.m900429200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of N-terminal Structure of TLR2-activating Lipoprotein in Staphylococcus aureus

Abstract: Staphylococcus aureus is known to activate mammalian immune cells through Toll-like receptor 2 (TLR2).We recently demonstrated that a lipoprotein fraction obtained from S. aureus by Triton X-114 phase partitioning is a potent activator of TLR2. In this study, we separated TLR2-activating lipoproteins expressed in S. aureus and characterized an N-terminal structure. The lipoprotein fraction of S. aureus was prepared by glass bead disruption followed by Triton X-114 phase partitioning. The TLR2-activating molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
59
4

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 35 publications
4
59
4
Order By: Relevance
“…The asymmetric distribution of fatty acids at the sn-1 and sn-2 positions of SitC lipoprotein was also confirmed in other S. aureus strains, including strains RN4220 and SA113, and in other lipoproteins, including lipoproteins SA1659 and SA2202 (data not shown). In contrast to our results, Tawaratsumida et al reported a single diacyl structure of an SA2202 lipoprotein modified with a 32:0 fatty acid, in which both the sn-1 and sn-2 positions are modified by the 16:0 fatty acid, from S. aureus SA113 cells grown in BHI medium for 6 h at 37°C (35). Apparently, their ␣-aminoacylation-free diacyl structure can be explained by their culturing conditions for the bacteria, such as the post-logarithmic-growth phase under acidic conditions as revealed in this study.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The asymmetric distribution of fatty acids at the sn-1 and sn-2 positions of SitC lipoprotein was also confirmed in other S. aureus strains, including strains RN4220 and SA113, and in other lipoproteins, including lipoproteins SA1659 and SA2202 (data not shown). In contrast to our results, Tawaratsumida et al reported a single diacyl structure of an SA2202 lipoprotein modified with a 32:0 fatty acid, in which both the sn-1 and sn-2 positions are modified by the 16:0 fatty acid, from S. aureus SA113 cells grown in BHI medium for 6 h at 37°C (35). Apparently, their ␣-aminoacylation-free diacyl structure can be explained by their culturing conditions for the bacteria, such as the post-logarithmic-growth phase under acidic conditions as revealed in this study.…”
Section: Discussioncontrasting
confidence: 54%
“…However, there are marked discrepancies between their study and ours. In fact, they detected only the diacyl form but not the triacyl form (35). Also, they iso- lated only one S-dipalmitoylglyceryl form rather than a series of diacyl and triacyl lipopeptide forms with different length fatty acids in the sn-1 and a 15:0 fatty acid in the sn-2 positions.…”
Section: Discussionmentioning
confidence: 98%
“…They showed that lipoprotein SitC was triacylated when Staphylococcus aureus was in the exponential-growth phase at neutral pH and diacylated in the post-exponential phase at low pH. This result explains the apparently contradictory findings reported in two papers published in 2009 in which Tawaratsumida et al demonstrated that one lipoprotein was diacylated whereas Kurokawa et al showed that another protein was triacylated (8,12). In their study, Kurokawa et al showed that acidic pH is not sufficient for the accumulation of diacylated proteins and that protein synthesis is also required.…”
contrasting
confidence: 47%
“…While in Gram-negative bacteria Lpp are further modified at the diacylglyceryl-cysteine by N-acyltransferase (Lnt), a homolog of Lnt was not identified in S. aureus, suggesting diacylated Lpp. The N-terminal part of an isolated staphylococcal Lpp was characterized as diacylated protein (9), whereas another study found evidence for triacylation of the Lpp SitC by a yet unknown enzyme (10).…”
mentioning
confidence: 99%